2021
DOI: 10.3390/app11167252
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Some Additives on the Properties of OPC Solidified Sandy Silt

Abstract: The ordinary Portland cement (OPC)-based solidification process is used extensively to reinforce soils due to its available and good bonding properties. Alternative products are used in cementitious materials to enhance the strength and to reduce OPC consumption. In this study, the effect of additive type and mass fraction on the microstructure and mechanical properties of solidified sandy silt are investigated. There are four types of additives (gypsum, lime, clay particles, and fly ash) at mass fractions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It was found that when the slag accounts for less than 60% of the solidification agent, the unconfined compressive strength of the solidified soil increases with the increase in the slag proportion. Wu et al [10] studied the use effect of cement composite additives on stabilizing silt, analyzed the effects of additive types and amounts on the mechanical properties and microstructure of stabilized soil, and found that the optimal mixing ratios of fly ash, clay, and gypsum were 4%, 4%, and 2%. Dhar et al [11] conducted clay solidification improvement experiments using plastic fibers and lime and conducted mechanical tests on solidified soil with different lime and fiber contents.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that when the slag accounts for less than 60% of the solidification agent, the unconfined compressive strength of the solidified soil increases with the increase in the slag proportion. Wu et al [10] studied the use effect of cement composite additives on stabilizing silt, analyzed the effects of additive types and amounts on the mechanical properties and microstructure of stabilized soil, and found that the optimal mixing ratios of fly ash, clay, and gypsum were 4%, 4%, and 2%. Dhar et al [11] conducted clay solidification improvement experiments using plastic fibers and lime and conducted mechanical tests on solidified soil with different lime and fiber contents.…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars have conducted extensive research on this topic. Wu et al [11] used cement composite admixtures to study the solidification of silt, studied the influence of different admixtures on the stability of soil mechanics characteristics and microstructure, and finally determined that the optimal mixing ratio of fly ash, clay, and gypsum is 4%, 4%, and 2%. Adhikari et al [12] used fly-ash-based geopolymers to improve medium-and high-plastic soils.…”
Section: Introductionmentioning
confidence: 99%